FROM ACADEMIC WRITING PORTFOLIO TO PUBLICITY PROJECT: PREPARING THE STUDENTS TO WRITING FOR PUBLICATION - Uzlifatul Masruroh Isnawati (Jurnal Bahasa Lingua Scientia, 2014)
This paper overviews the use of portfolios as  potential “source” in publishing journal applied in Academic Writing course. The first part presents the idea behind the use the students’ Academic Writing’s portfolio in preparing the students’ publication. The students work with their portfolio project, meanwhile the teacher takes part as the editor who asses and evaluate the students’ best portfolio. The second part, the project is initiated by stating the objective of the project where the  students are to produce one good article at the end of the Academic Writing course as the final product. Both teacher and the students are  engaged that the main purpose of the course is to produce an academic article, therefore during the teaching and learning  process,   the students  are  given an intense and comprehensive discussion  about academic writing as the core subject as well as the practicing and revising the students’ work as the feedback. The students practice on quoting,  paraphrasing, referencing, and summarizing in their writing. Finally, the teacher revises the students’work in every meeting until the final draft. An important aspect  to do is also dealing with ISBN (International standard book number) procedures as one of requirement in publishing a book. Unfortunately, the recent online procedure of ISBN was very helpful which enables the teacher to publish the edited students’ portfolio in to a book.